Influence of challenging work factors and employees’ well-being on knowledge sharing behavior in Saudi Aramco - Alghamdi, Mansour Ali A (2021)
Although previous research has demonstrated the impact of organizational components on employees, especially concerning their well-being, limited research has investigated the overall impact of innovative organizational culture (IOC) on employees’ well-being (EWB) and knowledge sharing behavior (KSB) (both tacit and explicit) in the oil and gas context. Therefore, based on the Conservation of Resources Theory and Maslow's Hierarchy of Needs, this study aims to investigate how employees’ well-being and knowledge sharing behavior can be managed within a challenging oil and gas workplace environment. It seeks to examine 1) the relationships between various work factors and employees' well-being in psychological, physical, and social aspects, 2) the relationships between employees' psychological, physical, and social well-being and knowledge sharing behavior (tacit and explicit), 3) the moderating effect of benevolent leadership on the relationship between challenging work factors and employees' physical, psychological, and social well-being, and 4) the moderating effect of innovative organizational culture (IOC) on the relationship between employees' physical, psychological, and social well-being with knowledge sharing behavior (KSB). This study employed the quantitative method and the survey technique was used for data collection. A total of 362 Saudi Aramco employees were recruited using judgmental sampling and Smart PLS and SPSS were used to analyze the data. The findings posit that 1) job hazards were found to significantly affect the employee's physical well-being; 2) better knowledge-sharing behavior in both tacit and explicit dimensions was demonstrated as a result of improved employees’ physical and social well-being. Specifically, tacit knowledge-sharing behavior was motivated by physical well-being while explicit knowledge-sharing behavior was motivated by social wellbeing; 3) In contrast to the initial prediction, workplace conflict was found to be positively related to social well-being. This could be due to the fact that Saudi Aramco welcomes open conflicts, where employees' sharing of different views, beliefs, and ii feelings do not bother others and instead brings them closer, resulting in enhanced wellbeing; 4) benevolent leadership has a significant moderating effect on the path between job hazard and physical well-being. It was found that under a high benevolent leadership condition, the negative relationship between job hazard and physical well-being was stronger. This is in contrast with the hypothesized direction. The finding thus suggests that Saudi Aramco employees believe that the presence of benevolent leaders does not reduce the impact of job hazard on physical well-being, but rather it makes them feel even more tired; 5) IOC was found to significantly moderate the path between social well-being and explicit KSB. In a high IOC condition, the positive relationship between social well-being and explicit KSB was stronger. Thus, the presence of the IOC condition enhances the impact of social WB on explicit KSB. Theoretically, this study adds further values to the pool of knowledge by recognizing three different types of employee well-being (psychological, physical, social) that contribute differently to knowledge sharing behavior. Also, it identifies conditions (moderators) where an employee’s well-being and knowledge sharing behavior can be strengthened. Practically, this study provides ideas to human resource management on strategies to enhance employees’ well-being for improved knowledge sharing behavior.